2003
DOI: 10.1143/jjap.43.l73
|View full text |Cite
|
Sign up to set email alerts
|

Protein Crystal Processing Using a Deep-UV Laser

Abstract: We study the level spacing distribution p(s) in the spectrum of random networks. According to our numerical results, the shape of p(s) in the Erdős-Rényi (E-R) random graph is determined by the average degree k and p(s) undergoes a dramatic change when k is varied around the critical point of the percolation transition, k = 1. When k 1, the p(s) is described by the statistics of the Gaussian orthogonal ensemble (GOE), one of the major statistical ensembles in Random Matrix Theory, whereas at k = 1 it follows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…We have developed novel techniques of protein crystal processing by femtosecond laser [1,2] and pulsed deep-UV laser [3][4][5]. The techniques, named as fs-CACO (femtosecond-laser-induced cut and cleave operation) and PULSA (pulsed UV laser soft ablation), are effective for processing and manipulation of protein crystals without significant damage.…”
Section: Abstract: Protein Crystal Processing Lasermentioning
confidence: 99%
“…We have developed novel techniques of protein crystal processing by femtosecond laser [1,2] and pulsed deep-UV laser [3][4][5]. The techniques, named as fs-CACO (femtosecond-laser-induced cut and cleave operation) and PULSA (pulsed UV laser soft ablation), are effective for processing and manipulation of protein crystals without significant damage.…”
Section: Abstract: Protein Crystal Processing Lasermentioning
confidence: 99%
“…To overcome these difficulties, we have previously utilized Deep UV solid and femtosecond lasers to process protein crystals. The risk of denaturation caused by heating can be suppressed by using these lasers with short pulse duration and high beam quality, which enable the processing of a variety of protein crystals [5][6][7][8][9][10][11]. However, these technologies have not yet been established for general use because they still have certain disadvantages to overcome.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that, when a femtosecond laser beam is tightly focused onto a transparent protein crystal in a transparent supersaturated solution in a sealed growth vessel, the crystal can be etched by multiphoton absorption [5]. We have also attempted processing protein crystals using a pulsed deep-UV laser [6,7] but found it difficult to perform processing in sealed growth vessels because the wavelength of the deep-UV laser brings about strong one-photon absorption in the crystal and in the supersaturated solution. Therefore, we consider that crystal processing by a femtosecond laser might be a suitable tool to conduct a series of systematic XRD measurements.…”
Section: Introductionmentioning
confidence: 99%